Echocardiographic Detection of Occult Diastolic Dysfunction in Pulmonary Hypertension After Fluid Challenge - Vineet Agrawal; Michele D'Alto; Robert Naeije; Emanuele Romeo; Meng Xu; Tufik R. Assad; Ivan M. Robbins; John H. Newman; Meredith E. Pugh; Anna R. Hemnes; Evan L. Brittain (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2019)
Background Identification of occult diastolic dysfunction often requires invasive right heart catheterization with provocative maneuvers such as fluid challenge. Non‐invasive predictors of occult diastolic dysfunction have not been identified. We hypothesized that echocardiographic measures of diastolic function are associated with occult diastolic dysfunction identified at catheterization. Methods and Results We retrospectively examined hemodynamic and echocardiographic data from consecutive patients referred for right heart catheterization with fluid challenge from 2009 to 2017. A replication cohort of 52 patients who prospectively underwent simultaneous echocardiography and right heart catheterization before and after fluid challenge at Monaldi Hospital, Naples, Italy. In the retrospective cohort of 126 patients (83% female, 56+14 years), 27/126 (21%) had occult diastolic dysfunction. After adjusting for tricuspid regurgitant velocity and left atrial volume index, E velocity (odds ratio 1.8, 95% CI 1.1–2.9, P=0.01) and E/e′ (odds ratio 1.9, 95% CI 1.1–3, P=0.005) were associated with occult diastolic dysfunction with an optimal threshold of E/e′ >8.6 for occult diastolic dysfunction (sensitivity 70%, specificity 64%). In the prospective cohort, 5/52 (10%) patients had diastolic dysfunction after fluid challenge. Resting E/e′ (odds ratio 8.75, 95% CI 2.3–33, P=0.001) and E velocity (odds ratio 7.7, 95% CI 2–29, P=0.003) remained associated with occult diastolic dysfunction with optimal threshold of E/e′ >8 (sensitivity 73%, specificity 90%). Conclusions Among patients referred for right heart catheterization with fluid challenge, E velocity and E/e′ are associated with occult diastolic dysfunction after fluid challenge. These findings suggest that routine echocardiographic measurements may help identify patients like to have occult diastolic dysfunction non‐invasively.